2017
DOI: 10.1111/aos.13612
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic features of cone‐rod dystrophy caused by pathogenic variants in the ALMS1 gene

Abstract: In summary, we can report that most of our ALMS patients primarily presented with nystagmus and severe photophobia since early childhood interestingly without night blindness in the absence of systemic symptoms. Only genetic testing analysing both nonsyndromic retinal disease (RD) genes and syndromic ciliopathy genes by comprehensive panel sequencing can result in the correct diagnosis, genetically and clinically, with important implication for the physical health of the individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 34 publications
(66 reference statements)
1
44
0
Order By: Relevance
“…The parents usually observe nystagmus (“wobbling eyes”), early onset photophobia (avoidance of light) and very poor visual contact. Visual symptoms occur early in the first months but some cases are later in onset with a slower evolution [ 20 , 21 ]. The first referral to an ophthalmologist occurs usually before the age of one.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The parents usually observe nystagmus (“wobbling eyes”), early onset photophobia (avoidance of light) and very poor visual contact. Visual symptoms occur early in the first months but some cases are later in onset with a slower evolution [ 20 , 21 ]. The first referral to an ophthalmologist occurs usually before the age of one.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Later global pigment mottling and local clumps can appear whereas classical “bone spicules” are seldom reported. Crystalline deposits have been observed [ 21 ]. Electroretinography (ERG) (mandatory) The usual characterization is an early onset severe cone-rod dystrophy and confirmation must be made by a full-field ERG.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Retinal disease in AS is an early-onset, severe, progressive retinal cone-rod dystrophy that begins in infancy and leads to blindness in childhood [82,84,85]. Marked photophobia and horizontal nystagmus develop within the first weeks to months of life.…”
Section: Retinal Disease In Asmentioning
confidence: 99%
“…Our patients have weight less than the 90 th percentile. Additionally, our patients both presented with high myopia, but previous studies primarily reported hyperopia in AS, ranging from mild to high, and mentioned only two cases of myopia [6,18,19,20,21,25,26,27,28]. Our patients have no family history of myopia, indicating that its development may be specific to these novel variants in ALMS1.…”
Section: Discussionmentioning
confidence: 56%
“…Alström syndrome most commonly presents with a cone-rod dystrophy, progressive sensorineural hearing loss, short stature, obesity, cardiomyopathy and various degrees of metabolic disturbances [6,18,19,20,21]. Most symptoms are typically begin in the first decade of life but there is a severety of the phenotypic spectrum [22].…”
Section: Discussionmentioning
confidence: 99%